The Impact of oil Prices on the Financial Performance of Banking Sector in Middle East Region - El-Chaarani, Hani (International Journal of Energy Economics and Policy, 2019)
The objective of this study is to determine the impact of oil price fluctuations on the financial performance of banking sector in 8 oil producing and exporting countries in Middle East region (Kingdom Saudi Arabia, United Arab Emirates, Qatar, Bahrein, Kuwait, Jordan, Oman, Iran) in the period between January 2012 and December 2017. The results do not reveal the same impact of oil price fluctuations on the financial performance of banking sector in each studied country. A significant direct impact of oil prices on the financial performance of banking sector has been found in Bahrein, Oman and Iran. In Jordan, Kuwait, Qatar, Saudi Arabia and United Arab Emirates, the results do not reveal any direct impact of oil price fluctuations on the financial performance of banking sector. The analysis also showed that the size of the economy in each country and its diversification in non-oil sectors have a direct impact on the relationship between oil price fluctuations and financial performance of banking sector. The existence of well diversified economy in non-oil sector reduces the direct impact of oil price fluctuations on the financial performance of banking sector. Keywords: Oil prices, Banks, Financial Performance, Macroeconomics Factors. JEL Classifications: E02, E44, E6, G21, Q41 DOI: https://doi.org/10.32479/ijeep.8075